A Framework for Developing, Implementing, and Evaluating a Social Determinants of Health Initiative. Issue 4 (July 2020) - Parrill, Rachael E.
Abstract : EXECUTIVE SUMMARY: Even while making progress toward improved health outcomes, the United States is facing health disparities, increasing rates of chronic diseases, and rising healthcare costs. Health systems and organizations understand the positive impact that addressing social determinants of health (SDOH) can have on population health outcomes and cost savings, yet barriers exist to SDOH initiatives because of a lack of standardization and a clear framework. This essay proposes six steps for various types of healthcare organizations to take to achieve their unique SDOH goals. The framework provides examples from the SDOH literature for identifying and prioritizing health issues; conducting literature scans; calculating a projected return on investment; and selecting, implementing, and evaluating an SDOH initiative. By applying the evidence base for SDOH in developing and evaluating their efforts, healthcare organizations are better equipped to implement an SDOH initiative that improves health outcomes and decreases healthcare costs.